2022
DOI: 10.1016/j.artd.2021.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Factors to Assess Risk for Postoperative Urinary Retention in Total Joint Arthroplasty: A Retrospective Analysis

Abstract: Background Postoperative urinary retention (POUR) is a significant problem in total joint arthroplasty (TJA). Although risk factors for POUR have been well documented, they are ubiquitous in an aging total joint population, which makes risk stratification difficult. The purpose of this study was to determine if a high preoperative post-void bladder scan identifies patients at risk for POUR. Methods A retrospective analysis was conducted on all TJAs performed at a high-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
1
9
2
Order By: Relevance
“…Notably, these findings depart from the principal conclusions of Magaldi et al. [ 12 ], who contend that PrePVR >50 mL is a predictor of POUR. Some methodological differences may account for this disagreement.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Notably, these findings depart from the principal conclusions of Magaldi et al. [ 12 ], who contend that PrePVR >50 mL is a predictor of POUR. Some methodological differences may account for this disagreement.…”
Section: Discussioncontrasting
confidence: 98%
“…The results of this study highlight that the use of bladder scanning preoperatively with a PrePVR >50 as a threshold may not be an effective screening modality for the risk of POUR. This is contrary to prior evidence suggesting that PrePVR of greater than 50 mL may serve as a useful screening tool [ 12 ]. Notably, these findings depart from the principal conclusions of Magaldi et al.…”
Section: Discussioncontrasting
confidence: 97%
“…Furthermore, in this study, we found that the preoperative use of the AUA symptom survey, widely used to detect symptoms of prostate enlargement or urinary problems, was not useful for predicting POUR in a TJA population. Although our study found no significant association with sex or age, younger patients undergoing TKA trended toward developing POUR, a finding also confirmed by our previous retrospective study 9 . With the increasing prevalence of outpatient TJA, this study addresses a potential impediment to discharge.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, Scholten et al reported that preoperative PVRV was associated with POUR following TJA but recommended against monitoring because it seemed to identify pre-existing voiding issues 14 . In a recent retrospective study that excluded patients with a history of urinary retention and bladder symptoms, we found increased catheterization with a preoperative PVRV of >50 mL in patients undergoing TJA 9 . Despite the evidence pointing to a clear association, there is no consensus that POUR is predictable at a specific residual volume.…”
mentioning
confidence: 75%
See 1 more Smart Citation